1994
DOI: 10.1007/bf00293316
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of growth hormone (GH) and glycoprotein subunit ? in GH-producing pituitary adenomas in acromegalic patients

Abstract: Thirty-one consecutive cases of pituitary adenoma in acromegalic patients were studied by immunohistochemistry. All adenomas contained cells immunoreactive with the anti-alpha-subunit of gonadotropic hormones (alpha; 0.6-53% of tumor cells) as well as with anti-growth hormone (GH; 4-74% of tumor cells). In serial section study, most cells immunoreactive with anti-alpha were identical to cells immunoreactive with anti-GH. There was a positive correlation between the percentages of cells immunoreactive for alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Monomorphous adenomas are defined as those that synthesize two or more hormones in the same cell. In bimorphous and plurimorphous adenomas, each hormone is produced by different cell populations, and almost all possible combinations of hormone productions involving GH and PRL, GH, PRL, glycoprotein hormone subunit ( GSU), TSH or FSH have been observed (Felix et al 1994, Furuhata et al 1994, Gessl et al 1994, Gil-del-Alamo et al 1994, Bertholon-Gregoire et al 1999. Although these combinations of hormones correspond to the differentiation of the cell lineages, it has been reported that very occasional cases of bimorphic pituitary adenomas produce adrenocorticotropic hormone (ACTH) and GH in different cell populations (Arita et al 1991, Kovacs et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Monomorphous adenomas are defined as those that synthesize two or more hormones in the same cell. In bimorphous and plurimorphous adenomas, each hormone is produced by different cell populations, and almost all possible combinations of hormone productions involving GH and PRL, GH, PRL, glycoprotein hormone subunit ( GSU), TSH or FSH have been observed (Felix et al 1994, Furuhata et al 1994, Gessl et al 1994, Gil-del-Alamo et al 1994, Bertholon-Gregoire et al 1999. Although these combinations of hormones correspond to the differentiation of the cell lineages, it has been reported that very occasional cases of bimorphic pituitary adenomas produce adrenocorticotropic hormone (ACTH) and GH in different cell populations (Arita et al 1991, Kovacs et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…In a further tumour, the acidophil stem cell adenoma, GH is co-expressed with PRL although it is rarely secreted in excess . Growth hormone-secreting tumours are also associated with the expression of thyroidstimulating hormone (TSH) or the common ␣-subunit of the glycoprotein hormones (Furuhata et al, 1994;Kovacs et al, 1982;Osamura and Watanabe, 1987;White et al, 1986). These associations reflect the Pit-1 regulated cell lineage in the normal gland.…”
Section: Pituitary Adenomas Classical Pituitary Hormonesmentioning
confidence: 96%
“…Multihormone production in monomorphous adenomas frequently includes combinations of GH, PRL, and TSHβ, or FSHβ and LHβ, which are derived from the same cell lineage that is dependent on Pit-1 and SF-1/GATA-2, respectively. In bimorphous and plurimorphous adenomas, each hormone is produced by a different cell population, and almost all possible combinations of hormone production involving GH and PRL, GH, PRL, glycoprotein hormone α subunit (αSU), TSHβ, and FSHβ have been observed (Felix et al 1994;Furuhata et al 1994;Gessl et al 1994;Gil del Alamo et al 1994;Bertholon Gregoire et al 1999).…”
Section: Introductionmentioning
confidence: 96%